Long Term Behavior of Composite Material Polyester-Wood Reinforced Glass Fiber - Olodo, E. T.; Niang, Fadel; Adjovi, E. C.; Kopnov, V. A. (My University, 2013)
If the industry generally considers composite materials as potentially interesting, the lack of durability makes their often limited employment. Indeed, the design of composite structures often requires taking account of the long-term behaviour under various types of complex solicitations. This study is based on the development of a methodology for modeling the long term behavior under constant load for multilayer composite structures subjected to complex solicitations. This study is on the evaluation of the long-term behaviour of tri-layers glass/polyester-wood composite material. The objective is the evaluation of the long term strength of this material by the Goldenblat-Kopnov criterion. The studied model is an orthotropic tri layer plate of sandwich type with upper and lower flanges (skins) are in composite material glass/polyester KACT-B and the intermediate layer (soul) is pine wood. The character of loading of the plate is reflected in the model by the functions σik(ξ), σmn(ξ) which can be of different natures. For example, to load in the long term by constant constraints in time (the weight own element for example), we will have: σik = const, σmn = const. The results of the calculations show that, for this type of material, the conditions of strength to the dangerous points of the plate are met.
Keywords: Goldenblat-Kopnov criterion; long term strength; tri layers composite